New insights in professional horse racing; "in-race" heart rate data, elevated fracture risk, hydration, nutritional and lifestyle analysis of elite professional jockeys. Issue 5 (4th March 2017) - O'Reilly, John; Cheng, Hoi Lun; Poon, Eric Tsz-Chun
ABSTRACT: Weight-making practices have been shown to impair musculoskeletal and physiological function of jockeys. This study investigated the "in-race" heart rate (HR) responses and hydration status during competitive racing, as well as selected physiological and lifestyle parameters of professional jockeys based in Hong Kong. "In-race" HR responses and early morning hydration status of 20 male jockeys were examined in hot and moderate climactic occasions. Additionally, bone mineral density (BMD), dietary intake and lifestyle choices were assessed. Osteopenia was observed in the calcanei of jockeys (left: 0.51 ± 0.06; right: 0.46 ± 0.12 g · cm −2 ). Energy and protein intake were significantly lower on a race day compared to a non-race day ( P < 0.05). "In-race" HRmax values were similar to those from VO2max laboratory tests (186 ± 14 vs. 185 ± 8 bpm). Hypohydration was observed on both racing days. (USG: 1.0247 ± 0.006 and 1.0256 ± 0.0258 mg · L −1 for hot and moderate conditions, respectively). Sauna usage (25.5%) and food restriction (20.4%) were the most common weight-making practices. Current lifestyle choices of jockeys result in suboptimal bone health, hydration status and nutritional intake, which can significantly enhance the fracture risk. Further research should develop exercise and nutrition guidelines for optimising their skeletal health.